Effect of the modulation ratio on the interface structure of TiAlN/VN and TiAlN/NbN multilayers: first-principles investigations - YaDong Huang; ZheHui Li; DaKai Zhang; TaiYu Xiao; ZhiPeng Pi; FangSheng Mei (Materials Research Express)
The interfacial structures of TiAlN/VN and TiAlN/NbN multilayers with different modulation ratios were studied using first-principles calculations. The results show that the interfacial bonding strength of TiAlN/VN remains relatively constant across different modulation ratios. In contrast, the interfacial bonding strength of TiAlN/NbN varies significantly with the modulation ratio. When the tTiAlN:tNbN ratio is 1:4, the simulated tensile and shear strengths of the TiAlN/NbN interface reach their highest values, 10.08 GPa and 5.13 GPa, respectively. This sensitivity arises from the modulation ratio’s influence on key parameters such as lattice mismatch, atomic packing, and localized orbital hybridization in the TiAlN/NbN system, which ultimately alter the interfacial bonding strength and structural stability. Analysis of fracture toughness reveals that surface energy is the primary factor governing its magnitude.